Expected early leaving among native and migrant students: Evidence from PISA for EU Member States - Ralph Hippe; Maciej Jakubowski (Publications Office of the European Union, 2022)
Early leavers from education and training become generally disadvantaged socially and economically in later stages in life, so it is important to understand better the motivations for early leaving and provide adequate policy solutions. This study analyses the factors that are most strongly related to the likelihood of leaving education and training early. It places special attention on migrant status, given the recent migration waves within and outside Europe, which are further exacerbated by the continuing war in Ukraine. To this end, we use the OECD most recent PISA data for 2015 and 2018 in a number of two-level logit regression models, including student- and school-level variables. The results show that migrant students do not differ structurally from EU natives in their likelihood of expected early leaving, implying that it is more important to focus on common factors.
Keywords: 370; Early leaving; Schüler; Migranten; Abbrecher; Bildungsverhalten; EU-Staaten